BALB/c and C57BL/6 Mice Cytokine Responses to Trypanosoma cruzi Infection Are Independent of Parasite Strain Infectivity - Ferreira, Bianca L.; Ferreira, Éden R.; de Brito, Marlon V.; Salu, Bruno R.; Oliva, Maria L. V.; Mortara, Renato A.; Orikaza, Cristina M. (Frontiers in Microbiology, 2018)
Trypanosoma cruzi is the etiologic agent of Chagas' disease, which affects 6-7 million people worldwide. Different strains of T. cruzi present specific genotypic and phenotypic characteristics that affect the host-pathogen interactions, and thus, the parasite has been classified into six groups (TcI to TcVI). T. cruzi infection presents two clinical phases, acute and chronic, both with distinct characteristics and important participation by the immune system. However, the specific contributions of parasite and host factors in the disease phases are not yet fully understood. The murine model for Chagas' disease is well-established and reproduces important features of the human infection, providing an experimental basis for the study of host lineages and parasite strains. Thus, we evaluated acute and chronic infection by the G (TcI) and CL (TcVI) strains of T. cruzi, which have distinct tropisms and infectivity, in two inbred mice lineages (C57BL/6 and BALB/c) that display variable degrees of susceptibility to different T. cruzi strains. Analysis of the parasite loads in host tissues by qPCR showed that CL strain established an infection faster than the G strain; at the same time, the response in BALB/c mice, although diverse in terms of cytokine secretion, was initiated earlier than that in C57BL/6 mice. At the parasitemia peak in the acute phase, we observed, either by confocal microscopy or by qPCR, that the infection was disseminated in all groups analyzed, with some differences concerning parasite tropism; at this point, all animals responded to infection by increasing the serum concentrations of cytokines. However, BALB/c mice seemed to better regulate the immune response than C57BL/6 mice. Indeed, in the chronic phase, C57BL/6 mice still presented exacerbated cytokine and chemokine responses. In summary, our results indicate that in these experimental models, the deregulation of immune response that is typical of chronic Chagas’ disease may be due to control loss over pro- and anti-inflammatory cytokines early in the acute phase of the disease, depending primarily on the host background rather than the parasite strain.